Do scientists have a responsibility to provide climate change expertise to mitigation and adaptation strategies? Perspectives from climate professionals. (February 2021) - Getson, Jackie M.; Sjöstrand, Anders E.; Church, Sarah P.; Weiner, Roberta; Hatfield, Jerry L.; Prokopy, Linda S.
Although the scientific community has reached a consensus that anthropogenic climate change is a severe and pressing issue, climate change remains a contentious debate with the United States public. Through a survey ( N  = 273), we explored climate professionals' perspectives on their role and responsibility to promote climate change adaptation/mitigation strategies related to agroecosystems. They believed that climate professionals have a social responsibility to provide scientific input to both policymakers and the public. There was strong agreement that media, political, and public support is necessary for development, and near unanimous agreement for implementation, of climate change mitigation/adaptation strategies. This study highlights the climate professionals' perceptions of their responsibility to provide scientific input, but also demonstrates that they believe the responsibility does not rest solely on their shoulders. Further research should explore scientists' perceptions of their and others' policy roles and scientists' interactions with different influencers of adaptation/mitigation policy.